Saberes experienciais docentes e suas potencialidades para formação de professores de ciências/biologia - Gatti, Mariana Donateli (2019)
This research aimed to understand how school contexts influence the construction of experiential knowledge of Science/Biology teachers. For this, we rely mainly on Tardif's ideas about teaching knowledge and Wersth's studies on mediated action, considering that experiential knowledge is built on the irreducible tension between the agents and the cultural tools they employ. We chose to produce the data through narratives from a focus group in which teachers discussed aspects related to school planning, classroom practice, and teacher work evaluation. Data analysis was performed using mediated action as a unit. Thus, we focus on the relationships established between the subjects and the mediation means they used to perform their actions. The results reveal that school contexts interfere in the construction of teaching experiential knowledge in several aspects. Institutional organization can influence the moment of exchange of experiences between peers, which influences the planning of interdisciplinary work and the possibilities for shared reflections. The resources present in schools interfere in the development of teaching practice as they enable or limit teachers' know-how. Another aspect that caught our attention was that, even with the many resources available in some schools, usually in private institutions, the choice or not to use them in practice may be linked to the opinions of other subjects who interact with teachers, such as example, the students themselves and their families. In this context, we have seen that, although mastering a certain cultural tool, it may or may not be appropriate by the teacher due to these interpersonal relationships and the discourses of power and authority that certain school agents exercise in the institutions. We note that external evaluations that fall on public institutions also influence teaching practice, as they generate a field of tension between management and teachers to ensure better results and, in turn, ensure a larger allocation of funds for institution. In addition, the bureaucracy that focuses teachers on tasks and curriculum content takes up a great deal of the time they have to plan and can stiffen lesson/teaching plans and, consequently, classroom practice. Although we have identified evidence of aspects that are more present in private schools, such as a greater presence of material resources and the strong influence of students' families on school dynamics; and aspects more present in public schools, such as the precariousness of material resources and greater freedom of teachers to make curricular adaptations, it is not possible and nor was it our intention to categorize these institutions, in view of the uniqueness of each context. Thus, even being in unique contexts of professional practice, and at different times of the teaching career, our results indicate that teachers share experiential knowledge. In this way, from this research emerged “Elements for a proposal for the formation of Science/Biology teachers that consider the teaching experiential knowledge”, which was constituted as the product of this work. Thus, we conclude that the experiential knowledge, which is part of the teaching knowledge, needs to be mobilized and further discussed in Science/Biology teacher education programs, in view of the possibility of contributing both to the teaching and learning process and to building a teacher’s professionalism.